2019
DOI: 10.3390/rs11212564
|View full text |Cite
|
Sign up to set email alerts
|

Using Vegetation Indices and a UAV Imaging Platform to Quantify the Density of Vegetation Ground Cover in Olive Groves (Olea Europaea L.) in Southern Spain

Abstract: In olive groves, vegetation ground cover (VGC) plays an important ecological role. The EU Common Agricultural Policy, through cross-compliance, acknowledges the importance of this factor, but, to determine the real impact of VGC, it must first be quantified. Accordingly, in the present study, eleven vegetation indices (VIs) were applied to quantify the density of VGC in olive groves (Olea europaea L.), according to high spatial resolution (10–12 cm) multispectral images obtained by an unmanned aerial vehicle (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 41 publications
1
22
0
1
Order By: Relevance
“…Once the stereo pairs of the images are taken from the UAV camera sensors, these are processed using known control points and orthorectified based on the digital surface model (DSM) produced by the triangulation of the stereo pairs [9]. In many applications, the detection of vegetated areas is essential, as in the case of monitoring agricultural areas or forests [10][11][12][13]. Even if vegetation is not a goal of a study, vegetation needs to be masked out to produce a digital elevation model (DEM) and provide realistic contours of the area.…”
Section: Introductionmentioning
confidence: 99%
“…Once the stereo pairs of the images are taken from the UAV camera sensors, these are processed using known control points and orthorectified based on the digital surface model (DSM) produced by the triangulation of the stereo pairs [9]. In many applications, the detection of vegetated areas is essential, as in the case of monitoring agricultural areas or forests [10][11][12][13]. Even if vegetation is not a goal of a study, vegetation needs to be masked out to produce a digital elevation model (DEM) and provide realistic contours of the area.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the unique response characteristics of vegetation in the near-infrared band, most vegetation indices (such as the normalized vegetation index [14] and the soil-adjusted vegetation index) are currently based on a combination of visible light and near-infrared bands [15]. At present, there are a variety of UAV-based multispectral minisensors on the market that can be used for vegetation monitoring [16][17][18][19][20][21][22][23] and can be selected according to the different needs of users. To make the VI products obtained from different sensors at different times comparable, the digital number (DN) of the collected image data is usually converted into reflectance, and then the reflectance is used to calculate the vegetation index [24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the accuracy of the CC estimation was also dependent on automatic thresholding using the Otsu method. Lima-Cueto et al, (2019), [42] used 11 VIs to quantify vegetation cover in olive groves, and they suggested that MS sensor-based CC had better accuracy as compared to RGB-based CC. A consistent observation in the aforementioned case studies was that RGB-based CC estimation was not efficient in the late season.…”
Section: Introductionmentioning
confidence: 99%